Modifikasi Serat Kenaf (Hibiscus cannabinus L.) Menggunakan Anhidrida Propionat - Eka Marya Mistar; Muhammad Muhammad (Jurnal Serambi Engineering, 2023)
Kenaf is a local crop that has great potential as a polymer composite reinforcement. However, the main weakness in strengthening composites using kenaf fiber is its hydrophilic or water-absorbing properties. To improve composite properties, surface modification of kenaf fiber is needed to enhance the structure and chemical properties of kenaf fiber. This study aims to explore the potential of chemical modification of kenaf fiber for use in composites. Chemical modification treatment of kenaf fibers was intended to improve the hydrophobicity that the compatibility between the fiber and matrix bonds are enhanced. In this study, chemical modification of kenaf fiber was performed using propionic anhydride. The modification process was done through a three-variation of retention time; 100, 200, 300 minutes at 100 C. This research also compared the kenaf fiber properties with and without the modification process, including the analysis of the weight percent gain and surface morphological structure. The results showed that the optimal weight gain and morphological structure was at a retention time of 200 minutes.